PENGARUH BROSUR TERHADAP PENGUASAAN MATERI DAN AKTIVITAS BELAJAR SISWA - Rizki Nofrial; Tri Jalmo; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2015)
This research aimed to know the influence of using brochure on conceptualunderstanding and student activity. Samples were X1 and X2 from SMAMuhammadiyah 1 Bandar Lampung 2013/2014 academic year that was choosen by purposive sampling. The research design was pretest-postest non equivalent. Quantitative data was obtained from the average value of pretest, posttest, and N-gain that were analyzed using test. Qualitative data students were obtained from activity and questionnaire. The result showed N-gain average of experiments class had medium category of 5,76. The result of students learning activities were in average of high criteria. Percentage of aspects of group work in solving the problems (79%); searching the information (74%); writing the alternative opinion idea from the solutions of problems (83%) presented the results of the discussion (89%), and asking questions (57%). Most of the students (89%) gave positive response to brocure.Thus, using brochure for learning was effective in improving student activity and conceptual understanding of environment. Tujuan penelitian ini untuk mengetahui pengaruh penggunaan brosur terhadap penguasaan materi dan aktivitas belajar siswa. Sampel penelitian adalah siswa kelas X1 dan X2 SMA Muhammadiyah 1 Bandar Lampung tahun pelajaran 2013/2014 yang dipilih secara purposive sampling. Desain penelitian adalah pretes postes tak ekuivalen. Data kuantitatif diperoleh dari nilai pretes,postes dan N-gain yang dianalisis secara statistik menggunakan uji t Data kualitatif adalah aktivitas dan angket tanggapan siswa. Hasil penelitian yaitu Rata-rata N-gain pada kelas ekperimen 5,76 (sedang). Pada aspek berkerja sama dalam memecahkan masalah (79%); mencari informasi (74%); menuliskan pendapat/ide alternatif solusi dari masalah (83%);mempresentasikan hasil diskusi (89%); dan mengajukan pertanyaan (57%) sebagian besar siswa (89%) memberikan tanggapan positif terhadap brosur. 'Sehingga pembelajaran menggunakan brosur efektif untuk meningkatkan penguasaan materi dan aktivitas siswa pada materi pokok lingkungan. Kata kunci: aktivitas belajar, brosur, lingkungan, penguasaan materi